Microservices best practices for Java - Hofmann, Michael; Schnabel, Erin; Stanley, Katherine (IBM Corporation, International Technical Support Organization, 2016)
Covering Microservices best practices for Java, this IBM Redbooks publication focuses on creating cloud native applications using the latest version of IBM WebSphere Application Server Liberty, IBM Bluemix and other Open Source Frameworks in the Microservices ecosystem. --
Number on resource description page: SG24835700. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed January 12, 2017)
Keywords: Java (Computer program language); Web applications; Application software -- Development; Java (Langage de programmation); Applications Web; Logiciels d'application; Développement; Application software; Development